Combination Therapy for Mycoplasma genitalium, and New Insights Into the Utility of parC Mutant Detection to Improve Cure . (4th January 2022) - Vodstrcil, Lenka A; Plummer, Erica L; Doyle, Michelle; Murray, Gerald L; Bodiyabadu, Kaveesha; Jensen, Jorgen S; Whiley, David; Sweeney, Emma; Williamson, Deborah A; Chow, Eric P F; Fairley, Christopher K; Bradshaw, Catriona S
Abstract: Background: Mycoplasma genitalium (MG) infection is challenging to cure because of rising antimicrobial resistance and limited treatment options. Methods: This was a prospective evaluation of the efficacy and tolerability of resistance-guided combination antimicrobial therapy for MG treatment at Melbourne Sexual Health Centre (August 2019–December 2020). All patients received 7 days of doxycycline before combination therapy based on the macrolide-resistant profile. Macrolide-susceptible infections received combination doxycycline + azithromycin (1 g, day 1; 500 mg, days 2–4) and macrolide-resistant infections combination doxycycline + moxifloxacin (400 mg daily for 7 days). Adherence and adverse effects were recorded at test-of-cure, recommended 14–28 days after antimicrobial completion. Sequencing was performed to determine the prevalence of single nucleotide polymorphisms (SNPs) in the parC gene and their association with moxifloxacin treatment outcomes in macrolide-resistant infections. Results: Of 100 patients with macrolide-susceptible MG treated with doxycycline + azithromycin, 93 were cured (93.0%; 95% confidence interval [CI], 86.1–97.1). Of 247 patients with macrolide-resistant MG receiving doxycycline + moxifloxacin, 210 were cured (85.0%; 95% CI, 80.0–89.2). parC sequencing was available for 164 (66%) macrolide-resistant infections; 29% had SNPs at parC S83 or D87 (23% S83I). The absence of SNPs at parC S83/D87 was associated with 98.3% cure (95% CI, 93.9–99.8) following doxycycline + moxifloxacin. The presence of the parC S83I-SNP was associated with failure in 62.5% (95% CI, 45.8–77.3). Side effects were common (40%–46%) and predominantly mild and gastrointestinal. Conclusions: Combination doxycycline + azithromycin achieved high cure for macrolide-susceptible infections. However, in the context of a high prevalence of the parC S83I mutation (23%) in macrolide-resistant infections, doxycycline + moxifloxacin cured only 85%. Infections that were wild-type for S83/D87 experienced high cure following doxycycline + moxifloxacin, supporting the use of a parC -resistance/susceptibility testing strategy in clinical care. Abstract : We assessed the efficacy of doxycycline followed by combination doxycycline + azithromycin for macrolide-susceptible MG and doxycycline + moxifloxacin for macrolide-resistant MG, with cure estimates of 93% and 85%, respectively. Sequencing revealed that a high rate of mutations causing quinolone-resistance underlies moxifloxacin-treatment failure.